Response Inhibition in the Parametric Go/No-Go Task and Its Relation to Impulsivity and Subclinical Psychopathy. Issue 3 (March 2017) - Weidacker, Kathrin; Whiteford, Seb; Boy, Frederic; Johnston, Stephen J.
The current study utilizes the parametric go/no-go task (PGNG), a task that examines changes in inhibitory performance as executive function load increases, to examine the link between psychopathic traits, impulsivity, and response inhibition in a cohort of healthy participants. The results show that as executive function load increased, inhibitory ability decreased. High scores on the Cognitive Complexity subscale of the Barratt Impulsivity Scale (BIS–11) predict poor inhibitory ability in the PGNG. Similarly, high scores on the Psychopathy Personality Inventory–Revised (PPI–R) Blame Externalization subscale predict response inhibition deficits in the PGNG, which loads more on the executive functions than the standard go/no-go task. The remaining BIS–11 as well as PPI–R subscales did not interact with inhibitory performance in the PGNG highlighting the specificity of associations between aspects of personality and impulsivity with inhibitory performance as cognitive load is increased. These data point towards the sensitivity of the PGNG in studying response inhibition in the context of highly impulsive populations and its utility as a measure of impulsivity.